Water monitoring with an automated smart sensor supported with solar power for real-time and long range detection of ferrous iron - Ozer, Tugba; Agir, Ismail; Borch, Thomas (ROYAL SOC CHEMISTRY, 2024)
Low-power and smart sensing systems for iron detection are necessary for in situ monitoring of water quality. Here, a potentiometric Fe2+-selective electrode (ISE) was fabricated based on cyanomethyl N-methyl-N-phenyl dithiocarbamate for the first time as an ionophore. Under optimal conditions, the ISE showed a Nernstian slope of 29.76 +/- 0.6 mV per decade for Fe2+ ions over a wide concentration range from 1.0 x 10-1 to 1.0 x 10-5 M with a lower detection limit (LOD) of 1.0 x 10-6 M. The ISE interference of various cations on the potentiometric response was also investigated. The ISE had a response time less than 3 s and the lifetime was two months. Also, an automated, long-range (LoRa), wireless enabled sampling microfluidic device powered with a solar panel as an autonomous power source was developed for a continuous sampling and sensing process. The sensing platform was employed in the determination of Fe2+ in acid mine drainage and spiked water samples with an average recovery of 100.7%. This simple, inexpensive (below $350), portable sensing platform will allow for rapid real-time monitoring of ground-, drinking-, and industrial waters contaminated with iron. A low-power and smart sensing system for in situ monitoring of iron in water samples.
Keywords: ACID-MINE DRAINAGE; ION-SELECTIVE ELECTRODES; RESPONSE-TIME; NEGATIVE PH; FERROZINE; MOUNTAIN; METALS; FE3+; FE2+; Chemistry